For whom do tablets make a difference? Examining student profiles and perceptions of instruction with tablets. (June 2021) - Hammer, Molly; Göllner, Richard; Scheiter, Katharina; Fauth, Benjamin; Stürmer, Kathleen
Abstract: Tablets are increasingly being used in classrooms, yet we know little about how students perceive instruction with tablets. Student perceptions come from the perspective of the learner and can reveal how technology-based teaching affects different learners. Using student ratings of supportive climate can show how supportive students perceive instruction with tablets and can begin to indicate effective integration of technology into the classroom. However, students' perceptions can vary within classrooms depending on their learning characteristics, suggesting distinct subgroups of students may perceive instruction with tablets in meaningfully different ways. The present study employs latent profile analysis to investigate differences in secondary students' perceptions depending on cognitive and motivational characteristics in classes with and without tablets (N =1, 058). Results indicate unmotivated and struggling students perceive more supportive climate in classes with tablets than the corresponding profiles perceiving instruction in classes without tablets. Furthermore, while students' perceptions seem to fall over time in classes that did not work with tablets, students' perceptions in classes with tablets remain more stable. Investigating both students' characteristics and their perceptions of supportive climate shows how different types of students are affected by the addition of tablets to the classroom. Highlights: Tablets present a new context of learning in German classrooms. Using student perceptions of support can show how tablets affect learning. Students perceive instruction differently depending on individual characteristics. Grouping students by profiles show tablets improve perceptions for some. Unmotivated students perceive more support with tablets.